Valorization of an Andean crop (Yacon) through the production of a yeast cell-bound phytase. - Conde Molina, Débora; Novelli Poisson, Guido; Kronberg, Florencia; Galvagno, Miguel Angel (My University, 2021)
The suitability of the yeast Schwanniomyces (f. Debaryomyces) occidentalis to produce phytase activity on a Smallanthus sonchifolius (yacon) extract-based medium (YSM) was studied. Optimal conditions for phytase production were evaluated in YSM at 28 ◦C and pH 5.5, with an inoculum of 107 cells/mL, in shaken flasks, using a Box-Benkhen optimization design, and analyzed by response surface methodology. Phytase location was determined by subcellular fractioning and protoplast formation. Maximum phytase titres were obtained with 0.11% w/v yacon reducing sugar, 0.65% w/v (NH4)2SO4 and 16 h of fermentation. The maximum phytase activity attained under these conditions was over 6-fold higher than in non-optimized medium. Scaling-up in a STR-type bioreactor further increased phytase productivity by 1.5-fold. Phytase produced was associated to the cell wall fraction, and presented optimal temperature and pH range values of 75–80 ◦C and 4.0–5.0, respectively, retaining 80% of its activity at 80 ◦C for 40 min. Progressively increasing phosphorus concentration in the medium inhibited enzyme production, up to 60% with 0.1% w/v KH2PO4. Yeast biomass, phytase production and production kinetics in YSM were similar to those produced in a cane molasses-based medium. Yacon resulted in a promising alternative feed stock to produce a yeast-bound phytase potentially applicable in the feed industry as a nutritional additive.
Keywords: UTN; Facultad Regional Delta; Feed industry; Nutritional additive; Yeast Phytase Schwanniomyces occidentalis; Smallanthus sonchifolius (Yacon)